Educação escolar indígena no Território Mendonça Potiguara - Costa, Dioclécio Bezerra da (2023)
The present dissertation aims to present an ethnography of indigenous school education, based on the indigenous schools located in the Amarelão community, namely: Escola Estadual Indígena de Ensino Fundamental e Médio Professor Francisco Silva do Nascimento and Escola Municipal Indígena Amarelão (formerly Escola Municipal Professora Alice Soares), located in the Municipality of João Câmara in the State of Rio Grande do Norte. The ethnography was carried out with the participation and involvement of the author himself with the investigated community, presenting dialogues with indigenous teachers and traditional leaderships that form the edu-cative community. In addition, the documentation from which these school units were constituted is evaluated. Thus, it has as results the advancement of public policies directed to indigenous people, such as the creation of the Commission for the Elaboration of the Indigenous School Policy of Rio Grande do Norte, to guide the specific public policies for indigenous education in the state. Therefore, it is necessary to question the relationship between culture, society, and school. This is because indigenous school education differs significantly from traditional schooling, since the learning process of these people has to go hand in hand with the strengthening of cultural identity